REPRESENTASI KEBENARAN (VERUM) DALAM DUNIA POLITIK DI INDONESIA: Usaha untuk Menciptakan Keadilan Sosial dalam Terang Immanuel Kant - Bendianto, Septian; Armada, Riyanto; Adon, Mathias Jebaru (Aggiornamento, 2024)
The author in this paper tries to examine the representation of truth (verum) in the world of politics in Indonesia as an effort to create social justice, by referring to the thoughts of Immanuel Kant. Kant argued that truth is an essential moral foundation in the formation of a just and civilized society. In the midst of Indonesia's political dynamics, this study identifies various aspects of truth representation in the context of public policy, governance, and citizen participation. An in-depth analysis of Kant's concept of truth reveals that efforts to create social justice in Indonesia depend on a shared understanding of moral values and ethical obligations. Along with that, the research highlights the challenges and obstacles that arise in everyday political practice, including corruption, inequality, and social injustice. The results show the need for reforms in political practice and governance to realize Kant's vision of a just society. This involves changes in political mindsets, the eradication of corruption, and increased active participation of citizens in policy-making. This research makes an important contribution in designing concrete steps to achieve social justice in Indonesia by integrating Kant's thoughts on truth and moral obligation into everyday political practice.